10.1016/s0967-0653(97)88991-0 (CrossRef Listing of Deleted DOIs, 2000)
Background Patient and public involvement (PPI) is increasingly recognized as an important component of inclusive and patient-centered health research. However, the extent and nature of PPI in autoimmune and inflammatory ocular disease research remain unclear and inconsistently reported. Objective This scoping review aims to map how patients and the public have been involved in research relating to autoimmune and inflammatory ocular diseases across clinical, translational, and preclinical domains. Methods This scoping review follows the methodological framework proposed by Arksey and O'Malley and refined by Levac, while incorporating elements of JBI guidance for scoping reviews. Reporting is informed by the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) checklist. The MEDLINE, Embase, and CINAHL databases were searched from inception to March 2025. Studies describing patient or public involvement in autoimmune or inflammatory ocular disease research were considered eligible for inclusion. Screening, data extraction, and thematic synthesis will be conducted using predefined eligibility criteria and a prepiloted charting form. Results Database searches were completed in March 2025. Following piloting of eligibility criteria and screening procedures, title and abstract screening commenced in April 2025. Full-text screening, data charting, and synthesis were planned sequentially in accordance with the protocol described, with completion of the review anticipated in December 2026. Findings from the completed scoping review will be disseminated through peer-reviewed publication, conference presentations, and patient advocacy networks. Conclusions This scoping review will provide the first comprehensive overview of how PPI has been implemented within autoimmune and inflammatory ocular disease research. Mapping current approaches and gaps may help support more meaningful integration of patient perspectives in future research and strengthen cocreation approaches within ophthalmology and autoimmune disease research.